2008
DOI: 10.1111/j.1365-2966.2008.13158.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-epoch spectroscopy of the globular cluster black hole in NGC 4472

Abstract: We present a study of the X-ray spectral properties of the highly variable X-ray emitting black hole in a globular cluster in the elliptical galaxy NGC 4472. The XMM-Newton spectrum of the source in its bright epoch is well described by a multiple blackbody model with a characteristic temperature $kT_{in}\approx$ 0.2 keV. The spectrum of an archival Chandra observation of the source obtained 3.5 years before the XMM data gives similar estimates for the blackbody parameters. We confirm that the fainter interval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 27 publications
5
32
1
Order By: Relevance
“…Shih et al (2008) also found that the spectral changes between the faint and bright phases in XMM04 were due to a lack of soft photons in the faint phase, which is consistent with our result for Obs ID 12888. . The diskbb plus PL model has fit the apparent hard excess much better than the previous models that only include one continuum component (see Fig.…”
Section: Hardness Ratiossupporting
confidence: 92%
See 3 more Smart Citations
“…Shih et al (2008) also found that the spectral changes between the faint and bright phases in XMM04 were due to a lack of soft photons in the faint phase, which is consistent with our result for Obs ID 12888. . The diskbb plus PL model has fit the apparent hard excess much better than the previous models that only include one continuum component (see Fig.…”
Section: Hardness Ratiossupporting
confidence: 92%
“…Both the Obs ID 12889 and 12888 spectra show suggestive evidence for a hard (>2 keV) excess. Shih et al (2008) also report a hard excess in their spectral analysis of the source. This feature may require an additional continuum component in order to fit properly.…”
Section: Continuum Plus Gaussian Spectral Modelmentioning
confidence: 94%
See 2 more Smart Citations
“…One other difference between these ULX populations is that those in star forming regions have hydrogen emission present in their optical spectra (e.g., Fabrika et al 2015), while at least three of the globular cluster ULXs have no hydrogen emission Irwin et al 2010;Roberts et al 2012). The most well studied GC ULX, RZ2109, also has very different X-ray behaviour from ULXs in star forming regions; it varies by more than an order of magnitude in X-ray luminosity between many different observations, but exhibits little or no variation in kT over those same observations (Shih et al 2008;Dage et al 2018). Several studies have considered the nature of the GC ULX sources and their optical emission, although most of them tend to focus on the source RZ2109 (e.g., Zepf et al 2008;Steele et al 2011a;Peacock et al 2012a,b;Steele et al 2014).…”
Section: Introductionmentioning
confidence: 99%